Nomenclatural notes and typification of Ophiorrhiza tonkinensis Pit. (Rubiaceae), an endemic species from Northern Vietnam - Quang, Bui Hong; Khang, Nguyen Sinh; Binh, Tran Duc; Ngoc Diep, Tran Thi; Kim Lien, Hoang Thi (Academia Journal of Biology, 2025)
The present article lectotypifies the name Ophiorrhiza tonkinensis Pit., a species endemic to North Vietnam. A thorough review of the literature and examination of the museum specimens did not assign a lectotype to the name O. tonkinensis. Therefore, according to Shenzhen Code, 2018, we designate the specimen currently held at P as the lectotype of O. tonkinensis. This specimen best matches the original description and possesses reproductive organs. Other specimens at P are incomplete or only have fruits, which do not represent all the characteristics described in the introduction. They are designated here as syntypes, presented by us in the article.The present article lectotypifies the name Ophiorrhiza tonkinensis Pit., a species endemic to North Vietnam.